EVALUATION OF THE STUNTING PROGRAM BUDGET PERFORMANCE AT THE SURABAYA CITY HEALTH DEPARTMENT IN 2025 - Aulia Jasmine Zalfania Azzahra; Kezhia Febrin Nadia Krista; Eva Hany Fanida; Ravienda Anita Fitrie (STMIK Indonesia Banda Aceh, 2026)
Stunting is a long-term malnutrition problem that affects the quality of human resources and is a development priority. The government uses the Special Allocation Fund (DAK) for the health sector to accelerate stunting reduction. This study aims to analyze the budget performance of the stunting program at the Surabaya City Health Office in 2025, evaluate the effectiveness of DAK use, and identify supporting and inhibiting factors. The method used was a descriptive qualitative approach with a Systematic Literature Review (SLR) and document analysis of scientific literature from 2019–2025 and official local government documents. The results indicate that the budget performance of the stunting program is quite effective and aligned with planning documents. The use of DAK supports nutrition interventions through community health center (Puskesmas) and integrated health post (Posyandu) services. However, effectiveness is less than optimal due to data inconsistencies between institutions, a lack of results-based performance indicators, and a suboptimal monitoring and evaluation system. Therefore, strengthening results-based evaluation, data integration, and improved cross-sectoral coordination are needed to ensure a more significant and sustainable program impact.